CGIAR Research Program on Fish - Plan of Work and Budget 2020 - CGIAR Research Program on Fish (CGIAR Research Program on Fish, 2020)
Country-level theories of change (ToCs) were developed in the following FISH focal countries in 2018: Bangladesh, Cambodia, Myanmar and Solomon Islands in the Asia-Pacific; and Egypt, Nigeria and Zambia in Africa. In 2019, informed by these country-level ToCs, the FISH Management Committee (MC) conducted a final review of the flagships (Sustainable Aquaculture (FP1) and Sustaining Small-Scale Fisheries (FP2)) and overall program ToC with reference to: (1) plausibility of delivery of planned research outputs and outcomes, (2) efficacy of pathways toward development outcomes and targets, (3) key change mechanisms and scaling strategies, and (4) research prioritization and investments. A key focus was on explicitly defining FISH pathways to achieve in delivering System Level Outcome 2 (Improve Food and Nutrition Security for Health) and on crosscutting outcomes, including those related to gender. The MC reviewed, adjusted and endorsed the ToC and related narratives, which are now revised and available on the FISH website.